A avaliação como instrumento de construção da autonomia dos educandos - CARVALHO, Hilda Catarina Xavier de (2022)
This work aims to analyze how teachers and students understand the evaluation process applied in the daily life of Elizabeth Farias Lobato Municipal Elementary School and its relation with the development of students' autonomy. The research is characterized as qualitative research and the instruments of data collection was the questionnaire and the documentary research, we used with the students a closed questionnaire and with the teachers an open questionnaire, besides analyzing school records and documents of the education secretariat of Catfish. The theoretical contribution used in this work was Hoffmann (1991,2000,2001,2003,2005), Luckesi (1990.1997,2002,2003,2005,2011), Freire (2000,2001,2004,2005,2011). Romão (2005) ), Which have contributed greatly to the development of the research. In this paper, we present the results of the research carried out by Gadotti and Romão (2012), Chizzotti (2009), Fernandes (2014), Padua (2004) and Richardson. In this way the research indicates that although the teachers present a certain advance in the understanding about the role of the evaluation in the learning teaching process, the practice of applying tests to verify the acquisition or not of the students' knowledge still exists, a practice that according to the research discusses, is detrimental to the day-to-day process of sharing and acquiring knowledge. This allows me to conclude that the concept and applicability of the evaluation process should rather be committed to the function of involving the student in the vast field of interaction between school knowledge and its conception of the world, so as to make it autonomous within of a procedural evaluation.